Analysis of Safety Riding Behavior of SMKN 2 Students Reviewed From Knowledge and Attitude - Yudhana, Amarin; Sari, Nia (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2018)
Safety riding is an effort made to reduce the number of traffic accidents and the impact of traffic accidents. In Indonesia traffic accidents have now become the third killer after heart disease and stroke. Kediri city statistical data in 2014 figures on traffic accidents show that most of the victims were teenagers with a total of 396 children (70%) with also the majority of teenagers with a total of 293 (79%), with most types of motorcycle 561 ( 78%). The purpose of this study is to analyze the safety riding behavior of students of SMK 2 Kediri city in terms of knowledge and attitude. The research method used is analytic survey with a cross-sectional approach. The population and sample are students of SMK 2 Kediri city taken by cluster sampling technique. The data obtained were analyzed by binary logistic regression test. The results of the study of 103 respondents showed the age of respondents 15-17 years with the sex of most women (76%). Most stated the system of giving pocket money in a daily way and on average ranged from Rp. 10,000, - per day. Respondents as a whole did not have a SIM and most started the first age of riding a motorcycle at the age of 10 years. The respondents' knowledge is mostly in the high category 70% and positive attitude 51.5%, but most respondents have bad behavior 73% in driving. The results of logistic regression analysis showed that there was an influence of knowledge on the Safety Riding behavior of students of SMK 2 Kediri city and there was no effect on attitudes towards Safety Riding Behavior of students of SMK 2 Kediri city. It is very important to increase students' knowledge regarding safety riding as an effort to minimize deaths due to accidents